Studi Kasus Tentang Peserta Didik Yang Sering Terlambat Datang Ke Sekolah Di SMA Negeri 11 Pontianak Barat - Simamora, Fetandralia Medita; Yuline, Yuline; Wicaksono, Luhur (Academy of Education Journal, 2024)
This research aims to find out and analyze in depth about students who are often late coming to school at SMA Negeri 11 West Pontianak. The case subjects in this study were two students. The method used in this research is descriptive with a qualitative approach in the form of a case study. The data collection techniques used are direct communication and documentation with data analysis techniques using case study steps including problem identification, diagnosis, prognosis, treatment, evaluation and follow-up. When providing treatment, researchers use the Behavioral counseling model. The implementation of counseling in case subject I uses aversion therapy techniques and positive reinforcement while in case subject II uses aversion therapy techniques and response formation. The factors causing the case subject to be late for school are due to internal and external factors. The results showed that there were significant changes in case subjects I and II after being given treatment four times. The changes in case subjects I and II are that students are not late, before the bell is rung the case subject is already present at school, disciplines themselves to manage daily time and is more eager to take part in learning.